2022
DOI: 10.1111/ddi.13611
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bird species recovery following high‐severity wildfire but in the absence of early successional specialists

Abstract: Aim:The distribution and abundance of forest biodiversity can be shaped by multiple drivers, including disturbances like wildfires. We quantified the influence of wildfire severity and bird life history attributes on temporal patterns of bird site occupancy.Location: Wet eucalypt forests of Victoria, Australia. Methods:We employed a Before, After, Control, Impact experimental design, gathering occupancy data on birds 5 years before, and for 10 years after, a wildfire in 2009.We quantified post-fire decline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…deviance information criterion, Akaike's information criterion—AIC; Vehtari et al, 2017). We considered models within 2 LOOIC units of each other to be equally supported by the data and a model with the lowest LOOIC that was >2 LOOIC units from the next best model to be best fit to the data (following Eisaguirre et al, 2019; Lindenmayer et al, 2022; Ravindran et al, 2021). To calculate LOOIC in this comparison, we used the log‐likelihood scores based on RGRi or Mortalityi, depending on whether it was a growth or mortality model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…deviance information criterion, Akaike's information criterion—AIC; Vehtari et al, 2017). We considered models within 2 LOOIC units of each other to be equally supported by the data and a model with the lowest LOOIC that was >2 LOOIC units from the next best model to be best fit to the data (following Eisaguirre et al, 2019; Lindenmayer et al, 2022; Ravindran et al, 2021). To calculate LOOIC in this comparison, we used the log‐likelihood scores based on RGRi or Mortalityi, depending on whether it was a growth or mortality model.…”
Section: Methodsmentioning
confidence: 99%
“…the data (followingEisaguirre et al, 2019;Lindenmayer et al, 2022;Ravindran et al, 2021). To calculate LOOIC in this comparison, we used the log-likelihood scores based on RGR i or Mortality i , depending on whether it was a growth or mortality model.…”
mentioning
confidence: 99%
“…Monitoring the changes in occurrence and abundance of wildlife communities over time is a core activity for conservation (Robinson et al 2018). Such data are critical in illuminating the effect of local management, the need for changes in management over time and the influence of broader environmental factors such as climate and weather that will have a significant effect on annual management decisions, including fire management (Lindenmayer et al 2022a). Birds can be important indicators of environmental change (Scheele et al 2019) and significant fluctuations have been reported as a consequence of severe rainfall deficits or surpluses (Connell et al 2022).…”
Section: Introductionmentioning
confidence: 99%